A participação do trabalhador na governamentalidade algorítmica do trabalho plataformizado através da negociação coletiva - Rafael Gontijo de Assis (2024)
This research is based on the struggle of platform workers for recognition and rights. Starting from a timeline regarding the morphology of work, the current context of work is the phenomenon of platform work, in which work relationships are no longer managed by a physical manager but by algorithms invisible to the human eye, but perceptible by workers. Management by algorithms goes beyond the bonds of the employment relationship, inserting itself into the worker's own social life, stripping him of his subjectivity as a worker and imposing an idea of entrepreneurship. Thus, labor platform companies are able to control not only the work, but also the worker's behavior. This research is based on the assumption that the relationship between the platform worker and the platform company has an evident employment nature and its main objective is to test the hypothesis of insertion of the platform worker in the construction of their employment contract, which is managed by the platform and organized through controls through applications, through collective bargaining. To this end, this research also had to go through its specific objectives, which are: a) to locate platform work as a current phenomenon of work organization and its effects generated by legislation; b) conceptualize algorithmic governmentality and how this form of government acts on workers; c) study the collective organization of these workers, especially the union, for the purposes of collective negotiation and d) the possibility of human insertion in algorithmic control. The methodology used was bibliographical research and jurisprudence. The result is that legislation has not evolved at the same pace as work organization. Platform workers are neglected by the judiciary, which does not recognize their rights as workers or their collective organization. It is also necessary to evolve legislation on the issue of control by algorithms and automated decisions, which, although recognized, require a more efficient regulatory apparatus. It is necessary to recognize the work of platform workers beyond the employment relationship in accordance with the legislation. Furthermore, it is necessary to recognize that these workers are social subjects, with organizational capacity and who demand rights and parity of participation in the work relationship that involves them.